2013
DOI: 10.1021/jf400318p
|View full text |Cite
|
Sign up to set email alerts
|

Glycoalkaloid and Calystegine Levels in Table Potato Cultivars Subjected to Wounding, Light, and Heat Treatments

Abstract: Potato tubers naturally contain a number of defense substances, some of which are of major concern for food safety. Among these substances are the glycoalkaloids and calystegines. We have here analyzed levels of glycoalkaloids (α-chaconine and α-solanine) and calystegines (A₃, B₂, and B₄) in potato tubers subjected to mechanical wounding, light exposure, or elevated temperature: stress treatments that are known or anticipated to induce glycoalkaloid levels. Basal glycoalkaloid levels in tubers varied between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
1
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 35 publications
7
66
1
23
Order By: Relevance
“…The content of glycoalkaloids in the flesh of tubers varied for α-solanine from 10.39 to 77.01 mg/kg FM, α-chaconine from 19.14 to 90.76 mg/kg FM and TGA 33.69 to 167.77 mg/kg FM (Table 2). Importantly, the TGA content did not exceed 200 mg/kg FM for any cultivar (equivalent to roughly 1000 mg/kg dry matter, assuming a water content of 80%), which is considered to be hazardous to human health (Tajner-Czopek et al 2012, Petersson et al 2013. The TGA contents found by us are in line with other literature data, which also indicates a significant variability in TGA ranges among cultivars.…”
Section: Glycoalkaloids Contentsupporting
confidence: 89%
See 2 more Smart Citations
“…The content of glycoalkaloids in the flesh of tubers varied for α-solanine from 10.39 to 77.01 mg/kg FM, α-chaconine from 19.14 to 90.76 mg/kg FM and TGA 33.69 to 167.77 mg/kg FM (Table 2). Importantly, the TGA content did not exceed 200 mg/kg FM for any cultivar (equivalent to roughly 1000 mg/kg dry matter, assuming a water content of 80%), which is considered to be hazardous to human health (Tajner-Czopek et al 2012, Petersson et al 2013. The TGA contents found by us are in line with other literature data, which also indicates a significant variability in TGA ranges among cultivars.…”
Section: Glycoalkaloids Contentsupporting
confidence: 89%
“…The TGA contents found by us are in line with other literature data, which also indicates a significant variability in TGA ranges among cultivars. Valcarcel et al (2014) indicated a range from 4 to 957 mg/kg dry matter (DM), Friedman et al (2003) from 5 to 592 mg/kg DM, Deusser et al (2012) from 7 to 466 mg/kg DM and Petersson et al (2013) indicated normal ranges between 5 and 100 mg/kg FM.…”
Section: Glycoalkaloids Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivars vary for light-induced glycoalkaloids (Grunenfelder et al 2006b). Some may increase eight-fold after illumination (Petersson et al 2013), while Percival (1999) identified the cultivar Maris Piper as being insensitive to lightinduced glycoalkaloid accumulation. Attempts have been made to use greening as a predictor of glycoalkaloids within particular genotypes (Dickie 2004).…”
mentioning
confidence: 99%
“…Wounding and light exposure are known to affect glycoalkaloid content, which could lead to levels beyond the threshold of 20 mg per 100 g fresh weight (Petersson et al 2013), the level considered safe for human consumption (Smith et al 1996). Many wild species of potato naturally produce high levels of glycoalkaloids (Gregory et al 1981), leading to a need to monitor glycoalkaloid content when introducing other traits from these species.…”
Section: Nutritionmentioning
confidence: 99%